Construct Validity of the Canadian Occupational Performance Measure in Participants With Tendon Injury and Dupuytren Disease. Issue 5 (1st May 2015) - van de Ven-Stevens, Lucelle A.W.; Graff, Maud J.L.; Peters, Marlijn A.M.; van der Linde, Harmen; Geurts, Alexander C.H.
Abstract : Background: In patient-centered practice, instruments need to assess outcomes that are meaningful to patients with hand conditions. It is unclear which assessment tools address these subjective perspectives best. Objective: The aim of this study was to establish the construct validity of the Canadian Occupational Performance Measure (COPM) in relation to the Disabilities of Arm, Shoulder, and Hand (DASH) questionnaire and the Michigan Hand Outcomes Questionnaire (MHQ) in people with hand conditions. It was hypothesized that COPM scores would correlate with DASH and MHQ total scores only to a moderate degree and that the COPM, DASH questionnaire, and MHQ would all correlate weakly with measures of hand impairments. Design: This was a validation study. Methods: The COPM, DASH questionnaire, and MHQ were scored, and then hand impairments were measured (pain [numerical rating scale], active range of motion [goniometer], grip strength [dynamometer], and pinch grip strength [pinch meter]). People who had received postsurgery rehabilitation for flexor tendon injuries, extensor tendon injuries, or Dupuytren disease were eligible. Results: Seventy-two participants were included. For all diagnosis groups, the Pearson coefficient of correlation between the DASH questionnaire and the MHQ was higher than .60, whereas the correlation between the performance scale of the COPM and either the DASH questionnaire or the MHQ was lower than .51. Correlations of these assessment tools with measures of hand impairments were lower than .46. Limitations: The small sample sizes may limit the generalization of the results. Conclusions: The results supported the hypotheses and, thus, the construct validity of the COPM after surgery in people with hand conditions.